Electronic Engineering students’ interactions through forums in the virtual component of a blended learning course - Alpala, Carol Anne Ochoa (Cuadernos de Lingüística Hispánica, 2014)
This article originates from a research project that gathers findings regarding social interaction in a group of students of ESP (English for Specific Purposes) in the virtual component of amixed learning environment.The group consistsof 23 ElectronicEngineering students from Universidad Santo Tomás in Tunja. Our purpose is to give evidence of the construction of knowledge andmeaning related to a specific subject, using technical English. In order to show how this community interacted and what this process represents in the experience ofEnglish learning in ahigher education context, interaction processes are reported on from a qualitative perspective through transcriptions of the forums, observations and the application of a survey. Results reveal that the Electronic Engineering students established a social bond that led themto become a virtual learning community in which they shared ideas, agreed on meaning and constructed knowledge through the use of English for Specific Purposes.